Age and gender demographics in social media use, Smartphone addiction and psychological morbidity among university undergraduates in Southwest Nigeria - TO Afe; OO Ogunsemi; BS Osalusi; OO Adeleye; AO Ale (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Smartphone addiction has become a public health issue. The use of social media has led to unintended consequences, especially among young adults and college students. Unfortunately, the pattern of use, the prevalence of addiction and the relationship with actual psychological morbidity are not clear. Objective: To evaluate the prevalence of Smartphone addiction and the relationship to the frequency of social media use and psychological morbidity among Nigerian university students. Method: One hundred and fifty-nine students were recruited through social media invites and direct invitation from Lecture Halls. The socio-demographic forms, the Smartphone Addiction Scale (Short Version) and Self-reporting Questionnaire-20 were administered. Results: WhatsApp was the most frequently accessed social media phone application (62.9%).Participants who used Instagram had the highest mean score on SAS-SV (31.4±9.4) and SRQ-20 (8.1±5.3). The prevalence of Smartphone addiction was 34.6% (55/159) while 48.4% (77/159) met the criteria for psychological morbidity. A higher proportion of males met the criteria for Smartphone addiction (29; 50.8%). Males had higher mean SAS scores (31.7±9.4) compared to the females (28.1±8.5) (p = 0.01). Smartphone addiction was more frequently associated with psychological morbidity among males (p = 0.01). No significant difference in Smartphone addiction and psychological morbidity was found across ages. Conclusion: Smartphone addiction is prevalent and associated with psychological morbidity among male undergraduates. There is a need to direct interventions at curbing its prevalence among undergraduates.